GRAVITY-ANTIGRAVITY INTERPLAY ON Mpc SCALE - Chernin, A. D. (Одеські астрономічні публікації, 2016)
It is demonstrated that the major physical features of the local expansion ﬂows of galaxies are due to antigravity domination in the dynamics of the systems.